E-Governance and its Impact on Improving the Quality of Strategic Decision: An Analytical Study at Baghdad Investment Commission - Abd-Alkareem, Bushra; Zahem Faisal, Muthana (Journal of Economics and Administrative Sciences, 2024)
The current study aims to know the impact of electronic governance in improving the quality of strategic decisions. The research was applied at Baghdad Investment Commission. The problem of the study was to identify the extent of the application of electronic governance and the degree of its impact on the quality of strategic decision. What are its dimensions and levels? how can public organizations provide their services in a way that meets the needs of their beneficiaries? Know the extent and impact of electronic governance’s dimensions on managers to percept the quality of strategic decision in the commission. The descriptive - analytical approach was relied upon, which is based on describing the phenomenon and then analyzing its causes and determining ways to copy with them. The researchers relied on the questionnaire form as a measurement tool it was distributed to a sample of 106 out of 110. It is represented by managers, heads of departments, divisions, and workers. A set of statistical methods were used to process the data, such as the arithmetic mean, KMO, SPSS, AMOS v.24, and standard deviation. The most important results that were reached were: Baghdad Investment Commission has websites in which data and information are constantly updated. It applies laws and punishes negligent parties within clear legal and seeks to reach good and decisive decisions. Research paper.